Pengembangan CNC Retrofit Milling untuk Meningkatkan Kemampuan Mesin Milling Manual Dalam Pemesinan Bentuk-bentuk Kompleks - Muhammad Kusumawan Herliansyah (Faculty of Engineering, Universitas Gadjah Mada, 2005)
In small-size mould manufacturing industry, milling process is an important element because this process consumes the longest produclion time. AIso, milling process needs great investments in tools. Most of the small-size mould manufacturing industries uses manual-milling machine for roughing process. Manual milling machine is used because of capacity limitation of the CNC milling machine and high investment of CNC machines.A prototype of low-cost CNC retrofit milling system is developed in this research, to enhance manual milling machine capabilities, in accuracy, speed, and process complexity. The advantage of the prototype results in reduced manufacturing cost and reduced lead time. This research also compare the capabilities of the prototype to others milling systems.The prototype results in accuracy of X axis and Y axis respectively 0.013 mm and 0.009 mm. This system is capable to set the feed rate of minimum 1 mm/min and maximum 250 mm/min, depending on the material being processed.Keywords: prototype, retrofit, CNC milling